Green synthesis, characterization, antibacterial, antioxidant and photocatalytic activity of Parkia speciosa leaves extract mediated silver nanoparticles - Ravichandran, V.; Vasanthi, S.; Shalini, S.; Shah, Syed Adnan Ali; Tripathy, M.; Paliwal, Neeraj (Results in physics, 2019)
The present study revealed the possible eco-friendly biosynthesis, biological activity and photocatalytic activity of Parkia speciosa leaf aqueous extract mediated silver nanoparticles. [Display omitted] •Green synthesis of silver nanoparticles using aqueous Parkia speciosa leaf extract.•Characterization of AgNPs was done by TEM, SEM, DLS, EDX and XRD.•Biosynthesised silver nanoparticle had good antimicrobial, antioxidant and photocatalytic activity.•The method was eco-friendly, benign and cost-effective. Green synthesis of silver nanoparticles (PAgNPs) was achieved by bio-reduction of silver nitrate using Parkia speciosa leaf aqueous extract. The PAgNPs formation was confirmed by UV–Vis spectroscopy. The synthesized silver nanoparticles in solution have shown maximum absorption at 410.5 nm, spectrophotometrically. The different parameters like temperature, pH, time, silver nitrate concentration and volume of leaf extract were optimized spectrophotometrically. The SEM, TEM and DLS analysis were used to confirm the average particle size of PAgNPs which were found to be 31 nm, 35 nm, and 155.3 d.nm, respectively. XRD and EDX analysis confirmed the nature and presence of silver. Synthesized PAgNPs showed significant photocatalytic (methylene blue under solar irradiation), antimicrobial (Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Bacillus subtilis) and antioxidant (DPPH radical scavenging method) activities. The developed method for the silver nanoparticles synthesis using Parkia speciosa leaf extract is an eco-friendly and convenient method. In near future, the synthesized PAgNPs could be used in the fields of water treatment, biomedicine, biosensor and nanotechnology.